General and specific combining abilities in a lulo diallel cross (Solanum quitoense Lam.) (2021)
Lulo (Solanum quitoense) is a promising agro-industry fruit tree, not only because of its nutritional value, taste, and appearance but also because it provides an alternative production system in mild and moderately cold climate zones. Lulo crop yield and production in the Department of Nariño (Colombia) has decreased in recent years when compared to other producing regions in Colombia. Therefore, the objective of this study was to estimate the effects of the general combining ability (GCA) and the specific combining ability (SCA) in a diallel cross of 10 promising parents in four growing regions of the Department of Nariño for use in breeding programs. A total of 45 hybrid combinations were obtained and assessed with Griffing method 4. The following variables were assessed: days to flowering onset (DFO), number of clusters per branch (NCB), fruit weight (FW), polar axis (PA) of the fruit, and yield (Y). The analysis of variance showed statistical differences for most variables in response to single-cross hybrid effects and locations, except for NCB and Y. Moreover, significant differences were found for the interactions between the GCA and SCA and the hybrids and locations, respectively, meaning that environment must be considered when selecting parents with specific adaptability. The effects of the GCA and SCA promoted higher positive values for the FW and Y in parents 4, 6, and 8 and their combinations. Therefore, these parental genotypes are promising for lulo genetic improvement programs since their additive effects and genetic dominance favor fruit weight and yield.